Human nonsense-mediated RNA decay regulates EMT by targeting the TGF-ß signaling pathway in lung adenocarcinoma. (10th September 2017) - Cao, Lu; Qi, Lisha; Zhang, Lin; Song, Wangzhao; Yu, Yue; Xu, Cong; Li, Lingmei; Guo, Yuhong; Yang, Lingyi; Liu, Changxu; Huang, Qiujuan; Wang, Yalei; et al.
Abstract: Nonsense-mediated mRNA decay (NMD) is a highly conserved pathway that selectively degrades aberrant RNA transcripts. In this study, we proved that NMD regulates the epithelial–mesenchymal transition (EMT) of lung adenocarcinoma (ADC). Moreover, we found that NMD core factor UP-frameshift 1 tends to be expressed at lower levels in human ADC tissues than in normal lung tissues, thereby raising the possibility that NMD may be downregulated to permit ADC oncogenesis. Our experiments in human ADC cell lines showed that downregulating NMD can promote EMT. Moreover, EMT can be inhibited by upregulating NMD. We tested the role of TGF-ß signaling and found that NMD influences EMT by targeting the TGF-ß signaling pathway. Our findings reveal that NMD is a potential tumor regulatory mechanism and may be a potential therapeutic target for ADC. Highlights: Nonsense mediated RNA decay (NMD) is an mRNA surveillance process. UPF1 is a key player among NMD process. UPF1 is significantly downregulation in lung ADC tissues, showing that NMD is downregulated to permit ADC oncogenesis. Downregulating NMD can promote EMT in ADC cell lines. And upregulating NMD can obvious inhibit the process of EMT. NMD through targeting the TGF-ß signaling pathway to regulate the process of EMT.